KEDUDUKAN HUKUM HAK ULAYAT MASYARAKAT HUKUM ADAT DIHUBUNGKAN DENGAN OTONOMI DAERAH (STUDI DI KECAMATAN HARIAN KABUPATEN SAMOSIR) - Mangapul Marbun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
The position of the customary rights of the customary law community in the Toba Batak community, namely the rights owned by a clan (State land), controlled, managed, utilized, the land and its contents for the needs of the citizens / descendants of the partnership as collective property that can be passed down from generation to generation (geneological) based on customary law. The UUPA recognizes the position of the ulayat rights of the customary law community in a formal juridical manner with discussion if in reality it still exists and does not conflict with the interests of the national, nation and state. The 1945 Constitution of the Republic of Indonesia Article 18-B paragraph (2), Article 28-I paragraph (3) The State recognizes and respects the customary public and their traditional rights as long as they are still alive. The cultural identity of traditional community rights is respected in accordance with the times and civilizations. The position of the customary rights of the Batak Toba community (land marga) in this study is still not as expected, in regulating and protecting laws from the past to the present, regulation and protection are still based on local customary laws. In Law No. 23/2014/9/2015 concerning Regional Government grants the authority of rights and responsibilities to provincial, regency / city governments to regulate and manage their own regions, one of the areas of defense based on the widest possible regional autonomy. The authority, rights and responsibilities of regional governments in regulating and protecting, managing their own ulayat rights (clan land) in certain areas are also in line with Presidential Decree No. 34 regarding policies in the defense sector, one of which is stipulation and is also in line with the government regulation of the Republic of Indonesia No. 38 Year 20007 concerning the Division of Government Affairs between the government and the Provincial Government of the Regency / City Government as a government affair which becomes the authority of the regional government towards the position of the ulayat rights of the customary law community in certain areas. In this study, in the Daily District of Samosir Regency. The authority, rights and obligations of Regional Government through stipulation in the form of Regional regulations have not been implemented, especially regarding local clan lands (ulayat rights of indigenous peoples). Therefore, this problem needs to be researched to get a true picture of the status of customary community rights in relation to regional autonomy in the Daily District of Samosir Regency. The results of this study, in the Samosir Kewenagan Regency Daily sub-district, the rights and obligations of regional government, it turns out that Tanah Marga (Hak Ulayat) is still regulated by local customary law, in fact the local government has the authority, rights and obligations to regulate and protect Ulayat Rights (Tanah Marga). certain by stipulation in the form of regional regulations, with the aim of providing legal certainty and benefits for the customary law community. Based on the research, it shows that the Land of Marga / Ulayat Rights of Indigenous Peoples in Harian District, generally in Samosir Regency, both horizontally and vertically until this research was conducted, there has been no settlement of certain customary rights of customary communities, in other words conflict resolution is still stagnant. The government needs to immediately establish the customary rights of customary communities in the form of a law. To ensure legal certainty / benefit and justice for all certain Customary law communities. Because ulayat rights are basically still found and still live according to the civilization of the Batak Toba people in the Daily District of Samosir Regency, which does not conflict with the development and interests of the Nation and the State.